2018
DOI: 10.22603/ssrr.2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three-dimensional rotational deformity correction in surgery for adult degenerative scoliosis using lumbar lateral interbody fusion and posterior pedicle screw fixation

Abstract: Abstract:Introduction: Corrective surgery for adult degenerative scoliosis using lateral interbody fusion (LIF) and additional posterior fixation is an efficient procedure. However, it is unclear how this procedure affects rotational deformity correction. Therefore, the goal of the present study was to use three-dimensional (3D) images, taken during surgery, to investigate rotational deformity correction in the treatment of adult degenerative scoliosis using LIF and posterior fixation using a pedicle screw sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Pedicle screw fixation is aided by 3D printing [ 14 ]. The three columns of the spine have a strong control force, and the internal fixation device is tightly mounted to the bone, thereby generating a strong correction force [ 15 , 16 ]. Suk conducted a retrospective analysis of scoliosis using the pedicle screw technique [ 17 ] and found that compared with hook fixation, pedicle screws treated more main thoracic curvature cases (55.8% vs 51.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Pedicle screw fixation is aided by 3D printing [ 14 ]. The three columns of the spine have a strong control force, and the internal fixation device is tightly mounted to the bone, thereby generating a strong correction force [ 15 , 16 ]. Suk conducted a retrospective analysis of scoliosis using the pedicle screw technique [ 17 ] and found that compared with hook fixation, pedicle screws treated more main thoracic curvature cases (55.8% vs 51.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Wound related complications including Wound infections, dehiscence, delayed healing, and seroma were reported in four studies in group L with a pooled rate of 7.5% (95% CI, 1 to 13.9) [ 18 , 20 , 22 , 23 ]. No significant difference was noted in comparison with group P with a pooled rate of 2.7% (95% CI, 1.1 to 4.3) across six studies [ 25 27 , 30 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Following initial screening of titles and abstracts, only 63 full-text articles in English were considered potentially eligible. After excluding 45 articles due to inadequate sample size (n=3), inadequate follow-up (n=3), review articles/case reports (n=10), outcome measures other than VAS/ODI (n=11), missing data like SD values (n=5), a heterogeneous cohort of patients (n=8), severe curves (n=2), and osteotomy/ ALIF as a primary procedure (n=3), only 18 articles met the inclusion criteria and were included in quantitative analysis [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 , 5 ] On the other hand, the direct vertebral rotation (DVR) technique using pedicle screws for vertebral rotational correction has been already proven to be useful in idiopathic scoliosis. [ 7 ] Although some reports have described the effects of LLIF and posterior corrective fusion on correcting rotational deformation, [ 8 , 9 ] these studies evaluated the final results of the combined techniques and did not assess the individual effects of LLIF and DVR on rotational correction. Thus, the purpose of this study is to investigate the individual corrective effects of LLIF and posterior corrective fusion surgery with DVR on vertebral rotation deformity in degenerative scoliosis.…”
Section: Introductionmentioning
confidence: 99%